2008
DOI: 10.1016/j.apmr.2007.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Ultrasonography for Clinical Medial Epicondylitis

Abstract: Our results indicate that ultrasonography is informative and accurate for the detection of clinical medial epicondylitis. Therefore, ultrasonography should be considered as an initial imaging method for evaluating medial epicondylitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 23 publications
1
48
4
1
Order By: Relevance
“…Rupture of the common extensor tendon of the wrist has been reported in athletes [2]. However, there are few reports in the literature that describe a complete tear of the common flexor tendon of the wrist [3,4]. In the present case report, we describe a complete tear of the common flexor tendon of the wrist in a 52-year-old housewife.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Rupture of the common extensor tendon of the wrist has been reported in athletes [2]. However, there are few reports in the literature that describe a complete tear of the common flexor tendon of the wrist [3,4]. In the present case report, we describe a complete tear of the common flexor tendon of the wrist in a 52-year-old housewife.…”
Section: Introductionmentioning
confidence: 56%
“…Park et al have classified the common flexor tendon pathology as tendinosis, partialthickness tear, or full-thickness tear. In their study, none of the 21 elbows of 43 patients who were examined had a full-thickness tear [3]. This indicated that a complete tear of the common flexor tendon of the wrist is a rare finding during ultrasound examination for medial elbow pain.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, we did not have information on the medical history of the body donors, and because of the advanced age of the donors, we found a much higher prevalence of alterations of the common flexor tendon than that described in the literature (13). A cadaver model also does not allow for color Doppler imaging, although the applicability of this method has already been shown (10).…”
Section: Biopsy and Histologic Analysismentioning
confidence: 86%
“…However, just more than half (55%) of all pathologic tendons were correctly identified by using each individual method. Park et al (10) published higher values for sensitivity (95%) of B-mode US by using clinical examination as the diagnostic standard. It is likely that this difference is related to early and low-grade tendinopathy of the common flexor tendon that is apparent at histologic examination but may be difficult to detect with US.…”
Section: Discussionmentioning
confidence: 99%